Antimicrobial activity of chitosan - Galimpin, Stella Marie C. (1999)
Chitosan was hydrolyzed into fragments for 6, 12, 24 and 36 hours. Molecular weight ranged from 8.4 x 10^4 to 7.4 x 10^4. Fragments were tested in bacteria, yeasts and molds,. Results showed that the microorganisms were more susceptible to chitosan hydrolyzed from 12 to 36 hours. Bacteria and yeasts were shown to be affected by fragment S12; molds, fragment S36. Upon increase in concentration bacteria became more sensitive to fragments S24 and S36. The polycationic nature of chitosan interferes with charged macromolecules found in the cell surface thus increasing permeability. Increased cell permeability was indicated by the increase in protein content of the supernatant from cell suspensions of chitosan treated cells and loss of definition of cell as observed in transmission Electron Microscopy (TEM). Corollary to this was the loss of cell osmolarity as manifested by the collapse in cell wall and agglomeration of intracellular components.